THE OFFENCE OF STALKING IN POLISH CRIMINAL LAW (ART 190A § 1 OF THE CRIMINAL CODE) - Mozgawa, Marek; Nazar, Katarzyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article discusses the statutory features of the offence of stalking, which is quite new in Polish criminal law systems. Therefore its present shape may lead to some controversies and cause some interpretation problems, especially in practice. This is important as there are many such offences detected each year.